Optimizing occupied memory of embedded software in the design phase - Hưởng, Phạm Văn; Bình, Nguyễn Ngọc; Thanh, Phạm Ngọc (Journal of Computer Science and Cybernetics, 2012)
Nowadays,  the optimizing embedded software plays an important role in the development of embedded software technology. The evaluation and optimization of embedded software in the design phase bring various benefits. In this paper, we propose a new method to optimize the occupied memory of embedded software in the design phase based on DSL, T4 and Topological sort. A program is specified as a chain of tasks and the relationship between the tasks. The program is expressed by the dependence graph as a directed graph. Each node in the directed graph describes a task, which consists of specification information such as name, input, output. Each edge describes the relationship between two tasks. The program working by order of tasks in the different Topological orders does not change the result, but the occupied memory and performances are different. From the dependence graph, we can find many topological orders, and each of them will have amount of occupied memory in difference. Therefore, we built a memory evaluation function to find the topological order that has the smallest amount of occupied memory.